Navigating Satisfaction in Smart Tourism: A Multi-Destination Study of Infrastructure, Safety, and Accessibility in Post-Pandemic Indonesia - Nur, Indrayani; Suriani, Seri; Abubakar, Herminawaty; Baharuddin, Sitti Mujahida; Salam, Ermawati Abdul; Vano, Vinson (Jurnal Aplikasi Manajemen, 2025)
As smart tourism evolves and health concerns grow post-pandemic, understanding what drives tourist satisfaction and revisit intention becomes increasingly urgent. This study investigates how smart tourism infrastructure, destination management communication, and perceived safety and hygiene affect tourist satisfaction and revisit intention, with perceived destination accessibility as a mediator. A quantitative survey was conducted among 380 domestic and international tourists who recently visited six major destinations in Indonesia. Using purposive sampling, respondents with experience using digital tourism services were selected. Data were analyzed using PLS-SEM via SmartPLS 4, with reliability, validity, and bias control checks. Results show that all three independent variables significantly influence tourist satisfaction, both directly and through the mediating role of destination accessibility. Tourist satisfaction, in turn, strongly predicts revisit intention. This study introduces perceived safety and hygiene into the smart tourism framework and highlights the critical role of accessibility in shaping satisfaction. The findings offer practical insights for destination managers and policymakers seeking to enhance tourism experiences and visitor retention in smart, health-conscious environments.